The complete mitochondrial genomes of the higher termites Labiotermes labralis and Embiratermes neotenicus (Termitidae: Syntermitinae) - Vincent Hervé; Andreas Brune (Mitochondrial DNA. Part B. Resources, 2017)
The complete mitochondrial genomes (mitogenomes) of two higher termites were reconstructed from the metagenomes of individual gut compartments with more than 2000-fold coverage. The circular mitogenomes of Labiotermes labralis (accession number KY436201) and Embiratermes neotenicus (accession number KY436202) have a length of 15,935 and 15,868 bp and an overall G + C content of 30.7 mol% and 33.7 mol%, respectively, and both have an asymmetric nucleotide composition. Genome structure and orientation are the same as in other termites and in the ancestral insect mitogenome. These data further expand arthropod mitogenome databases, which have become an important resource in ecological, phylogenetic and evolutionary studies.